Malay symbols in Hashim Hassan’s paintings / Norul Azlina Mohamed - Norul Azlina, Mohamed (2017)
Artist’s around the world uses ‘symbols’ as a way to convey certain message in their artworks. A number of artist’s in Malaysia also applied the same thing in their artworks as a way to deliver something. Unfortunately, the uses of symbols in the artworks can sometimes pose a problem to the audience due to understanding its meaning. This study was made to clarify the meaning embedded in the works of Hashim Hassan. This is due to how he repeatedly uses a lot of Malay symbols such as Sulur Bayur, cosmos, Pohon Beringin, flora, moon, Wau Bulan, stork (bangau), Kepala Perahu, Bunga Budi and Pucuk Rebung in his paintings. For that reason, a qualitative descriptive study was adopted to analyze Hashim Hassan’s earlier works. The study will also be focusing on the meaning of the symbols used by him from Malay philosophy and perspectives in order to facilitate deeper understanding of Malay symbols. Significance of each symbol will also be unwrapped to find the relationship with the particular Malay culture. The analysis of the selected paintings will be based on Edwin Panofsky theory. It was found that Malay symbols have different meaning and application where the same symbols also used by other culture in the world. It was found that Malay symbols can be applied in any surface related to Malaysian perspectives as a whole. By having this clarification about its meaning and philosophy, symbols can become a study on its own and more research about other symbols can be conducted in the future. By compiling the symbols and its meaning in a catalogue might benefit students in secondary and primary school as well as universities and higher institution. This is a way to nurture the love for our culture and heritage.